2013
DOI: 10.1053/j.gastro.2013.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Gene Expression Signature for Patients With Hepatitis C–Related Early-Stage Cirrhosis

Abstract: Background & Aims Liver cirrhosis affects 1%–2% of population and is the major risk factor of hepatocellular carcinoma (HCC). Hepatitis C cirrhosis-related HCC is the most rapidly increasing cause of cancer death in the US. Non-invasive methods have been developed to identify patients with asymptomatic, early-stage cirrhosis, increasing the burden of HCC surveillance, but biomarkers are needed to identify patients with cirrhosis who are most in need of surveillance. We investigated whether a liver-derived 186-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
225
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(237 citation statements)
references
References 37 publications
4
225
0
5
Order By: Relevance
“…The prognostic 35‐gene signature was implemented in the digital transcript counting (nCounter) assay (NanoString) 19. Total RNA (200–400 ng) was assayed according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The prognostic 35‐gene signature was implemented in the digital transcript counting (nCounter) assay (NanoString) 19. Total RNA (200–400 ng) was assayed according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Gene signatures associated with tumor liver tissues allowed the prediction of early recurrence [9,18] and patient survival [7] after surgery. Interestingly, some studies reported gene expression signatures associated with the non-tumor adjacent liver tissue that provide an additional value in prognosis prediction [19,20,21,22] (table 2). …”
Section: Microarray Technology Application On Hccmentioning
confidence: 99%
“…Microarray technology has been also used to study gene expression to predict HCC outcome in non-tumor liver tissue, usually affected by chronic hepatitis or cirrhosis, [19,20,21,22]. In 2008, Hoshida et al [19 ]reported a 186-gene signature from liver tissue adjacent to the tumor that predicted survival after surgery for HCC and also predicted the outcome of liver cirrhosis.…”
Section: Gene Signatures Associated With the Non-tumor Liver Tissuementioning
confidence: 99%
“…In this regard, several genetic expression profiles with prognostic significance have been suggested (51)(52)(53)(54)(55)(56)(57). However, to date, it has not been shown that the presence of a specific molecular pattern allows a concrete therapeutic decision.…”
Section: Refining Prognostic Assessment and Therapeutic Decisionmentioning
confidence: 99%